Kajian Prasarana Pendidikan Sekolah Dasar sebagai Salah Satu Indikator Pencapaian Standar Nasional Pendidikan - Relisa -- (Jurnal Pendidikan dan Kebudayaan, 2016)
This study aimed to study the level of achievement of primary school infrastructure standards in Banjarmasin City. This method of the research was intended to obtain data of the achievement of educational infrastructure. Results of the study showed that the level of achievement of primary school infrastructure reached 60,94%. This level of achievement still seems to be low partly due to the lack of insfrastructure which is still owned by the school. In addition, although the school already has the infrastructure of education, the quality conditions of many infrastructures suffered heavy damage so it unfit for use. Types of infrastructure its educational echievement is higher than average includes: classroom, the boardroom, the teachers’s room, and playground. On the contrary, the educational infrastructure is below average achievement including: school’s health unit, library, and restroom. The conclusion of this study is that the achievement of educational infrastructure in Banjarmasin city has not met the requirements of education national standards. ABSTRAK Penelitian ini bertujuan untuk mengkaji tingkat ketercapaian standar prasarana pendidikan sekolah dasar di Kota Banjarmasin. Penelitian ini menggunakan metode survei. Hasil kajian menunjukkan bahwa tingkat ketercapaian prasarana pendidikan sekolah dasar mencapai 60,94%. Tingkat ketercapaian yang tegolong rendah ini antara lain disebabkan oleh masih minimnya prasarana yang dimiliki sekolah. Di samping itu, kondisi kualitas prasarana banyak mengalami kerusakan berat sehingga tidak layak untuk digunakan. Jenisjenis prasarana pendidikan yang ketercapaiannya di atas rata-rata meliputi ruang kelas, ruang pimpinan, ruang guru, dan tempat bermain. Sebaliknya, prasarana pendidikan yang ketercapaiannya di bawah rata-rata meliputi ruang UKS, ruang perpustakaan, dan jamban(toilet). Penelitian ini menyimpulkan bahwa ketercapaian prasarana pendidikan di kota Banjarmasin belum memenuhi persyaratan standar nasional pendidikan.